THE EFFECT OF ACCOUNTING INFORMATION SYSTEMS QUALITY, TRUST AND LOYALTY ON USER PERFORMANCE USING EXTENDED INFORMATION SYSTEM SUCCESS MODEL ON MULTIFINANCE COMPANY IN DEPOK - Arinda Pramesti (Jurnal Ilmiah Ekonomi Bisnis, 2019)
Globalization resulted in fiercer competition between the companies. To be top in the competition, companies must have good management in achieving the company's main objectives and obtain the maximum benefit effectively, efficiently and economically. Currently, the company has used information technology to carry out its business activities. However, any technology used by the company should always be evaluated, whether the use of these technologies provide a good contribution to the user and also companies that use them. This research is aimed to obtain empirical evidence of relationship between accounting information system quality, trust and loyalty of system with user performance. This study uses updated D&M IS Success Models categories to measure the system. Those categories are System Quality, Information Quality, Service Quality, System Use, User Satisfaction, and Net Benefits. This research has used questionnaires which were proceed and analyzed by multiple regression analysis method. The process of data analysis are validity and reliability test, classic assumption test, multiple regression analysis, and hypothesis testing analysis. The hypothesis analysis uses simultaneous regression analysis. The results show that System Quality, Information Quality and Service Quality have a significant effect on Use and User Satisfaction simultaneously. Use and User Satisfaction have a significant effect on Net Benefits, Trust and Loyalty simultaneously. Net Benefits, Trust, and Loyalty have a significant effect on User Performance simultaneously.